Corporate responses to complaints : the impacts on public's purchase intentions. - Lau, Pei Wen. (2008)
Growing importance of service excellence and customer satisfaction can be attributed to the intensifying competition amongst companies. Complaint handling and service recovery have taken an increasingly important role as companies strive to gain market share and to positively affect customer repurchase intention. Much research has been done on the impact of service recovery on repurchase decision of customers but little has been said on the effects of corporate responses on the purchase or repurchases intention of third-party consumers. This study aims to determine if corporate responses to complaints published in the media have an impact on public’s purchase (or repurchase) intention.